Position sensorless and optimal torque control of reluctance and permanent magnet synchronous machines - De Kock, Hugo Werner (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Electric and Electronic Engineering))--University of Stellenbosch, 2009.